Mycosynthesis of Metal-Containing Nanoparticles-Fungal Metal Resistance and Mechanisms of Synthesis - Šebesta, Martin; Vojtková, Hana; Cyprichová, Veronika; Ingle, Avinash P; Urík, Martin; Kolenčík, Marek (International journal of molecular sciences, 2022)
In the 21st century, nanomaterials play an increasingly important role in our lives with applications in many sectors, including agriculture, biomedicine, and biosensors. Over the last two decades, extensive research has been conducted to find ways to synthesise nanoparticles (NPs) via mediation with fungi or fungal extracts. Mycosynthesis can potentially be an energy-efficient, highly adjustable, environmentally benign alternative to conventional physico-chemical procedures. This review investigates the role of metal toxicity in fungi on cell growth and biochemical levels, and how their strategies of resistance, i.e., metal chelation, biomineral formation, biosorption, bioaccumulation, compartmentalisation, and efflux of metals from cells, contribute to the synthesis of metal-containing NPs used in different applications, e.g., biomedical, antimicrobial, catalytic, biosensing, and precision agriculture. The role of different synthesis conditions, including that of fungal biomolecules serving as nucleation centres or templates for NP synthesis, reducing agents, or capping agents in the synthesis process, is also discussed. The authors believe that future studies need to focus on the mechanism of NP synthesis, as well as on the influence of such conditions as pH, temperature, biomass, the concentration of the precursors, and volume of the fungal extracts on the efficiency of the mycosynthesis of NPs.
Keywords: fungus; Bioaccumulation; biosynthesis; green synthesis; nanomaterial; biologický transport; metal oxide nanoparticle; Catalysis; redukční činidla; metallic nanoparticle; Reducing Agents; bioakumulace; kovové nanočástice; Metal Nanoparticles; biomolecule; Biological Transport; katalýza